Investigating the Effect of miR-145-5p Inhibition with an Antisense Oligonucleotide on Experimental Autoimmune Encephalomyelitis - McKay, Kelsea (Université d'Ottawa / University of Ottawa, 2022)
Multiple Sclerosis (MS) is a chronic, inflammatory disease of the central nervous system. MS is caused by the immune-mediated destruction of myelin and oligodendrocytes, resulting in demyelination and neurodegeneration. The microRNA miR-145-5p has been demonstrated to be upregulated in MS lesions. Our lab has previously shown that dysregulation of miR-145-5p can interfere with oligodendrocyte differentiation in mice and that knockout of miR-145-5p protects mice from experimental autoimmune encephalomyelitis (EAE), a model for MS. The objective of this study is to determine if inhibition of miR-145-5p with an antisense oligonucleotide (ASO) is sufficient to protect mice from EAE. Female mice were induced with EAE and then treated with a control or miR-145 ASO at the onset of disease. We evaluated disease progression by monitoring clinical severity, and evaluating molecular and structural characteristics of EAE by RT-qPCR, histology, immunohistochemistry and electron microscopy. We have shown that the miR-145 ASO reduced miR-145-5p expression in the lumbar spinal cord, spleen and thymus following EAE induction. Treatment with the miR-145-5p ASO resulted in improved clinical severity of EAE, reduced neuroinflammation and increased myelination. Inhibition of miR-145-5p may represent a novel treatment for MS.
Keywords: Multiple Sclerosis; Experimental Autoimmune Encephalomyelitis; Remyelination; microRNAs; Antisense Oligonucleotide; Oligodendrocyte